Epidemiological and clinical characteristics of hospitalized unintentional injuries among children in central China from 2017–2023 - Wang, Meng; Cheng, Yibing; Wang, Haijun; Lin, Li; Shen, Yuelin (Frontiers in Pediatrics, 2024)
Objectives: To examine the epidemiological and clinical characteristics of hospitalized unintentional injuries among children in Central China and theoretically propose preventive and control measures.We conducted a retrospective study of children aged 0-18 years with unintentional injuries who were admitted to a tertiary hospital in Central China from January 2017 to December 2023. We examined various aspects of the unintentional injuries, including age, gender, urban-rural distribution, external causes, trends, location of injury, cost, and length of stay.Results: A total of 20,166 children with hospitalized unintentional injuries were enrolled. The median age with IQR was 2.8 (1.6, 5.1) years, with majority of the patients (57.0%) were aged 1-3 years, while the fewest were aged 11-18 years. The male-to-female ratio was 1.8:1, and the urban-to-rural ratio was 1.1:1. The most common external causes were foreign bodies (41.7%), exposure to inanimate mechanical forces (25.1%), and falls (22.1%). The most frequently injured body parts were head (72.5%). The total number of unintentional injuries exhibited an increasing trend from 2017 to 2022, and a decreasing trend from 2022 to 2023. The urban-rural distribution reversed after 2020. The overall hospitalization cost was 20,810,870.4 USD, with an median cost of 758.7 (556.4, 1186.2) USD per person.Unintentional injuries imposed a heavy burden on society and families.However, the number of cases and the urban-rural distribution showed significant trend changes from 2017 to 2023. The external causes varied by age group, gender, and region, while prevention and control measures should be developed accordingly.